Seed-Specific Over-Expresson of an Arabidopsis cDNA Encoding a Diacylglycerol Acyltransferase Enhances Seed Oil Content and Seed Weight - Jako, C.; Kumar, A.; Wei, Y.; Zou, J.; Barton, D.L.; Giblin, E.M.; Covello, P.S.; Covello, P.S.
We recently reported the cloning and characterization of an Arabidopsis (ecotype Columbia)diacylglycerol acyltransferase cDNA (Zou et al., 1999)and found that in Arabidopsis mutant line AS11, an ethyl methanesulfonate-induced mutation at a locus on chromosome II designated as Tag1 consists of a 147-bp insertion in the DNA, which results in a repeat of the 81-bp exon 2 in the Tag1 cDNA. This insertion mutation is correlated with an altered seed fatty acid composition, reduced diacylglycerol acyltransferase (DGAT; EC 2.3.1.20)activity, reduced seed triacylglycerol content, and delayed seed development in the AS11 mutant. The effect of the insertion mutation on microsomal acyl-coenzyme A-dependent DGAT is examined with respect to DGAT activity and its substrate specificity in the AS11 mutant relative to wild type. We demonstrate that transformation of mutant AS11 with a single copy of the wild-type Tag1 DGAT cDNA can complement the fatty acid and reduced oil phenotype of mutant AS11. More importantly, we show for the first time that seed-specific over-expression of the DGAT cDNA in wild-type Arabidopsis enhances oil deposition and average seed weight, which are correlated with DGAT transcript levels. The DGAT activity in developing seed of transgenic lines was enhanced by 10